EXPLORING ABANDONED TERRITORIES AND THEIR TOURISM POTENTIAL - Amazaryan, A. (SUSh Scientific Proceedings, 2025)
In the field of modern tourism, there is a unique and attractive direction — the study of abandoned places or so-called "ghost territories". These places, where life was once in full swing, are now forgotten by the society, remaining silent witnesses of time. Their restoration, the elimination of unattractive images have become urgent tasks. The topic is not only relevant, but also deeply fascinating, since it contributes to the sustainable development, the economic progress and the preservation of historical and cultural values. It stimulates innovative approaches, reduces the isolation of such places and enriches cultural and social interaction. Expected results of the work:  The development of an innovative methodology and tools for assessing the tourism potential of abandoned territories;  The creation of a comprehensive package of optimal models and strategies for tourism development in abandoned territories. In the modern world, interest in sustainable tourism and environmental protection is growing. The process of turning abandoned territories into tourist attractions can stimulate the economic recovery of these regions due to: Creation of new jobs; Attracting investment; Support for the development of local communities; Improvement of environmental quality. Moreover, such an approach contributes to the preservation and transfer of cultural heritage to future generations, opening up opportunities for the development of innovative tourism products and formats. Unlocking the tourism potential of abandoned territories requires interdisciplinary research that can serve as a basis for new management methods, approaches and development of tourism infrastructure in these territories